Diseño de una estrategia de transformación digital para la empresa Colombiana de Logística - Link (2019)
The present work, is about the design of a digital transformation strategy, for a company that provides the freight transport service in Colombia; as a result of this, a research was made related with the principal aspects that characterize the digital transformation and the fourth industrial revolution. Then, a diagnosis of the sector and the company was made, in order to establish the strategies for digital transformation, work planning and a financial evaluation.